Research and application of UMR technology for new metropolitan area network - Yuanyang YIN; Zhizhong WANG; Youqiang JIANG; Jiaqi SUN; Xiaobin LIANG (Dianxin kexue)
The new metropolitan area network adopts the new architecture of spine-leaf.BRAS is a high hanging and centralized deployment mode.With the deployment of the new metropolitan area network, the home wide service is gradually cut over to the new network.The current typical bearer scheme has many problems, such as the sharp increase of pressure on the network equipment MAC routing table, the large and complex network configuration.After analyzing and comparing the defects of typical bearer schemes, the implementation scheme of UMR technology was innovatively put forward, which provided reference significance for promoting the rapid deployment of new metropolitan area network.